Konsumsi Bahan Kering Dan Bahan Organik Ternak Domba Lokal Yang Mendapt Suplementasi Rumput Laut (Gracilaria Sp) Dan Chromium (Cr) Organik Dalam Pakan - Triya Farida Nugrahani; Caribu Hadi Prayitno; Munasik Munasik (Fakultas Peternakan Universitas Jenderal Soedirman, 2020)
Background. The purpose of this study was to examine the amount of dry matter consumption and organic matter in sheep feed supplemented with seaweed (Gracilaria sp) and organic Chromium minerals. Materials and methods. The material was used 18 local rams farmed for 3 months. The research was carried out with experiments in vivo. The method used was a completely randomized design (CRD) with 3 treatments and 6 replications. The treatments tested were R0 = control feed (55% concentrate and forage 45%), R1 = feed R0 + seaweed flour 3.6%, R2 = feed R1 + 0.03 ppm chromium. The observed variables were the consumption of dry matter and organic matter. Results. The results of the analysis of variance showed that the use of 3.6% seaweed flour and 0.3 ppm organic Cr as a supplement in sheep's feed did not affect the consumption of dry matter and organic matter. The average results of consumption of dry matter sheep feed research results, R0 724.21 g/head/day or 3.12 % body weight, R1 798.99 g/head /day or 3.30 % body weight and R2 884.41 g /head/day or 3.63 % body weight. The average consumption of sheep's Organic Matter were Ro 518.45 g / head /day or 2.23 % body weight, R1 510.72 g/head/day or 2.09 % body weight and R2 602.47 g/head /day or 2.47 % body weight. Conclusion. The conclusion was that the use of seaweed flour and organic Cr as a supplement in sheep's feed does not affect dry matter and organic matter intake in sheep's feed.